Harnessing the power of amnion-chorion membrane in periodontal therapy: A comprehensive review - Ritu Agrawal; Aditya Sinha; Shailendra S Chauhan; Satendra Sharma (Wolters Kluwer Medknow Publications, 2024)
Amnion-chorion membrane (ACM) has emerged as a versatile biomaterial with immense potential in various medical and dental applications, including periodontal therapy. ACM possesses unique properties, including a bioactive matrix rich in growth factors, anti-inflammatory and antibacterial attributes, and a remarkably thin, self-adherent structure. These characteristics make ACM well suited for various periodontal applications, such as intrabony defect treatment, gingival recession management, socket preservation, papillary preservation, and sinus membrane repair. This review offers comprehensive details of the properties, applications, and implications of ACM membranes in the realm of periodontal treatment.